The Use of Gamification in Mathematics Education: Enhancing Geometry Comprehension with High School Students - Espinosa-Pinos, Carlos (2024)
The non-existence or non-application of strategies, methodologies, innovative techniques such as gamification, which offers a more attractive and dynamic way of approaching the mathematical topic about the equation of the line, a concept that is often abstract and difficult to understand for many students. The present study aims to analyze the effectiveness of gamification in the pedagogical process between educators and learners in relation to the understanding of the equation of the line in students of the tenth year of higher EGB. This analysis was carried out through a quantitative approach that included the administration of a knowledge test before and after applying gamification to 92 GBS tenth grade students. These students were divided into two groups of 46 students each, one experimental group (EG) worked on gamification activities and the other control group (CG) employed traditional techniques. The purpose of this division was to determine if there were significant differences in performance means between the two groups. The gamified proposal incorporates elements of games, challenges, rewards and competitions, taking into account the learners in a dynamic way, providing them with a sense of purpose and achievement. After the T-Student application, it was concluded that the proposal not only significantly increases the academic performance of the students, but also develops logical thinking and reasoning, and favors autonomous and collaborative work.